A study on the health concept and hygienic practices during Menustration among Mannan tribes of Kerala - Soumya Devasia
Puberty has been recognized as a special period among the girls in India, which signifies the transmission from girlhood to womanhood. This transmission period is marked with an important milestone ‘menarche’. In Indian culture, the community inter-related with respect to traditions, myths, superstitious believes and attitudes especially about the menstruation and related issues. Menstruation period is generally considered as unclean in India, it is considered as ‘pollution’ period among traditional Hindus of all the strata people of India. The specific foods are given to the puberty attained girl to strengthen her feminine identity. The present study tries to understand the knowledge, believe system, attitudes, taboos and practices relating to the menstruation among Mannan tribes of Kerala.